Efficacy and safety of selinexor in the treatment of AML: A protocol for systematic review and meta-analysis. Issue 49 (10th December 2021) - Yu, Liming; Yin, Xuewei; Si, Yuping; Wang, Yan; Wang, Jingyi; Cui, Siyuan
Abstract: Background: Acute myeloid leukemia (AML) is the most common leukemia among the adult population and accounts for about 80% of all cases. Despite advancements in therapeutic regimens, the prognosis remains very poor, especially in the elderly population. Selinexor is a first-in-class, oral, small molecule Exportin-1 inhibitor that is being developed for the treatment of a variety of cancers, including AML. The efficacy and safety issues of selinexor in the treatment of AML are still the focus of attention. Therefore, we conducted a meta-analysis to evaluate the efficacy and safety of selinexor in the treatment of AML. Methods: According to the search strategy, regardless of publication date or language, randomized controlled trials of selinexor for AML will be retrieved from 8 databases. First of all, the literature was screened according to the eligibility criteria, and use the Cochrane Collaboration's tool to assess the quality of the included literature. Then, using Rev Man 5.3 and STATA 14.2 software for traditional meta-analysis. Finally, the evaluation of the quality of the evidence and the strength of the recommendations will adopt the Grading of Recommendations, Assessment, Development, and Evaluation method. Results: This study will evaluate the efficacy and safety of selinexor for AML, thereby providing more evidence support for clinical decision-making in AML. Conclusion: Our research will provide more references for the clinical medication of patients with AML.